Pengaruh Konseling Behavioral Teknik Assertive Training untuk Mereduksi Adiksi Internet Siswa Sekolah Menengah Pertama - Nurhanifah, Astri; Arizona, Arizona; Sari, Syska Purnama (Prodi Bimbingan dan Konseling Fakultas Keguruan dan Ilmu Pendidikan | Universitas Islam As-Syafi'iyah, 2024)
Internet addiction is a condition where individuals cannot control themselves in using the internet which causes negative tendencies that have a negative impact on physical health, psychology, and social relationships. The purpose of the study was to determine the effect of behavioral counseling services assertive training techniques to reduce the internet addiction of junior high school students. The research method used in this study is a quantitative approach with a Quasi experimental method with a one group pre-test and post-test design. The results of this study indicate that: the results of hypothesis testing obtained a value (2 Tailed) of 0.068 which indicates that Ha is accepted because the sig value> 0.05. And Ho is rejected because the sig value is 0.068> from 0.05 so this shows that there are changes in the pre-test results before implementing behavioral counseling assertive training techniques and post-test after implementing behavioral counseling assertive training techniques